Utilization of local coal in Pakistan's oil-fired power plants and future clean technologies for power generation - Qamar Abbas; Haseeb Yaqoob; Uzair Sajjad; Hafiz Muhammad Ali; Muhammad Musaddiq Jamil (Case Studies in Chemical and Environmental Engineering)
Pakistan possesses extensive lignite coal reserves that remain underutilized due to their low quality and reliance on imported oil for power generation. This study examines the feasibility of using local coal to replace oil in power plants while meeting global and local emission standards. The research explores clean coal technologies like Underground Coal Gasification (UCG) combined with Integrated Gasification Combined Cycle (IGCC) and carbon capture systems to mitigate environmental impact. Economic, environmental, and technical comparisons with renewables highlight UCG-IGCC as a cost-effective, sustainable solution for Pakistan's energy challenges, offering pathways to reduced emissions and greater energy self-sufficiency.